Performance Assessment of Concrete Structures and Engineered Barriers for Nuclear Applications Conclusions of RILEM TC 226-CNM - L'Hostis, Valérie; Gens, Robert; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
The main outcomes of RILEM TC-226-CNM are summarized in this book. Key input was provided by researchers from countries that are main contributors in the R&D, design, construction, operation, and regulation of waste nuclear reinforced concrete facilities. Nuclear power plants and many of the facilities and structures used for the management of radioactive waste materials generated by the fuel cycle use concrete in their construction. RILEM TC 226 CNM covered several areas including functional and performance requirements for concrete structures; degradation processes; phenomenological modelling, field experiences, tests approaches, instrumentation and monitoring methods dedicated to performance assessments; service-life models; aging Management of Nuclear Power Plants, repair techniques; codes and standards specific to radioactive waste facilities.  .
1 Some definitions and terminology -- 1.1 Service Life -- 1.2 Long-term behaviour -- 1.3 Ageing Management -- References -- 2 Materials and Properties -- 2.1 Introduction -- 2.2 Blended cements and hydrated phase prediction -- 2.3 Characterization of low pH-cementitious materials -- 2.4 Fiber reinforced and advanced cement-based materials -- 2.5 Transport Properties -- 2.6 Coupled Phenomena and Materials Behaviour -- 2.7 Carbonation and Oxidation of Cementitious Materials -- 2.8 Leaching -- 2.9 Desiccation and pre-cracking in cement pastes and mortars -- 2.10 Understanding Durability and Performance in the Context of Specific Applications -- 2.11 Integration for Application to Engineering Systems -- 2.12 RILEM TC-226-CNM recommendations for future R&D -- References -- 3 Corrosion -- 3.1 Introduction -- 3.2 Corrosion of metals in concrete for nuclear applications -- 3.3 Corrosion mechanisms -- 3.4 Corrosion modelling -- 3.5 Corrosion test programmes -- 3.6 Effects of concrete cracking on corrosion behaviour -- 3.7 RILEM TC-226-CNM recommendations for future R&D -- References -- 4 Aging Management of Concrete Structures of NPPs -- 4.1 Introduction -- 4.2 Aging Management of Concrete Structures of NPPs -- 4.3 Conclusion -- 4.4 RILEM TC-226-CNM recommendations for future R&D -- References -- 5 Waste Management and Performance Assessment -- 5.1 Introduction -- 5.2 Role and durability of cement barriers in waste storage and disposal -- 5.3 Impact of gas generation and carbonation of cement systems -- 5.4 Conclusions -- 5.5 RILEM TC-226-CNM recommendations for future R&D -- References -- 6 Conclusions.  .
Keywords: Materials -- Analysis; Nuclear engineering; Civil engineering; Radiation dosimetry; Characterization and Analytical Technique; Nuclear Energy; Civil Engineering; Radiation Dosimetry and Protection